A Prospective Study on Profile of Gynaecological Problems in Adolescent Girls at a Tertiary Care Centre - Nidhi Gupta; Ankita Srivastava; Neha Varun; Arifa Anwar; Aruna Nigam (Shiraz University of Medical Sciences, 2020)
Background: Gynaecological problems of adolescents occupy a special and very important place in the spectrum of gynaecologicaldisorders. Keeping this background in mind, this study was done to find the gynaecological problems of the adolescents attendinggynaecological OPD and emergency with the aim to study type of problems, causative factors and treatment modalities.Methods: It is a cross-sectional study done in outpatient department of Obstetrics & Gynaecology Department of HamdardInstitute of Medical Sciences & Research over a period of one year. Data was collected with the help of a pre- designed, pretestedquestionnaire after taking proper informed written consent from the unmarried adolescent females with age 11-19 years.Quantitative data is tabulated in numerical value as percentages.Results: In our study, most of the adolescents were the students of primary or secondary level educational status. The maincomplaint by adolescent girls in our study was menstrual problems (n=124,75.1%) including irregularity in flow, bleeding, bleeddays, occurrence of menses and pain. Menstrual problem was followed by vaginal discharge (n=43, 26%). The main diagnosiswas PCOD which was in 23 girls followed by vaginal discharge in 17 participants and urinary tract infection in 16 girls.Conclusion: A very empathetic attitude and special attention should be given to the adolescent population.